From Fluid Identities to Sectarian Labels: A Historical Investigation of Indonesia’s Shi‘i Communities - Chiara Formichi (Al-Jami'ah: Journal of Islamic Studies, 2014)
Since 2011 Indonesia has experienced a rise in intra-Muslim sectarian violence, with Shi‘a and Ahmadi communities becoming the target of radical Sunni groups. Taking as point of departure the attacks on Shi‘a Muslims and the rapid polarization of Sunni and Shi‘i identities, this article aims at deconstructing the “Shi‘a” category. Identifying examples of how since the early century of the Islamization devotion for the Prophet Muhammad and his progeny (herein referred to as ‘Alid piety) has been incorporated in the archipelago’s “Sunni” religious rituals, and contrasting them to programmatic forms of Shi’ism (adherence to Ja‘fari fiqh) which spread in the socio-political milieu of the 1970s-1990s. This article argues not only that historically there has been much devotional common ground between “Sunni” and “Shi‘a”, but also that in the last decade much polarization has occurred within the “Shi‘a” group between those who value local(ized) forms of ritual and knowledge, and those who seek models of orthopraxy and orthodoxy abroad.[Sejak tahun 2011, kekerasan bernuansa aliran dalam internal muslim di Indonesia mengalami peningkatan, dengan komunitas Syiah dan Ahmadiyah menjadi sasaran kekerasan dari kelompok-kelompok Sunni radikal. Berangkat dari kasus penyerangan terhadap kelompok Syiah dan cepatnya polarisasi identitas Sunni-Syiah, artikel ini berusaha mendekonstruksi kriteria “Syiah” di Indonesia. Beberapa contoh praktik keagamaan menunjukkan bahwa sejak awal proses Islamisasi di nusantara, pengagungan terhadap diri Nabi dan keturunannya (dalam hal ini adalah keluarga ‘Alī ibn Abī Ṭālib) telah menyatu dalam ritual-ritual keagamaan kelompok Sunni. Artikel ini menunjukkan bahwa tidak hanya secara historis terdapat banyak kesamaan antara “Sunni” dan “Syiah” di Indonesia, bahkan juga terjadi polarisasi pada beberapa dekade terakhir di tengah penganut Syiah antara kelompok yang memilih bentuk-bentuk ritual dan pengetahuan local dengan kelompok yang mencari rujukan ortodoksi dan ortopraksi dari luar.]